Get the most out of your questions with IDNLearn.com's extensive resources. Discover reliable and timely information on any topic from our network of experienced professionals.

Choose the equation that represents the solutions of [tex]\(0 = 0.25x^2 - 8x\)[/tex].

A. [tex]\(x = \frac{0.25 \pm \sqrt{(0.25)^2 - (4)(1)(-8)}}{2(1)}\)[/tex]
B. [tex]\(x = \frac{-0.25 \pm \sqrt{(0.25)^2 - (4)(1)(-8)}}{2(1)}\)[/tex]
C. [tex]\(x = \frac{8 \pm \sqrt{(-8)^2 - (4)(0.25)(0)}}{2(0.25)}\)[/tex]
D. [tex]\(x = \frac{-8 \pm \sqrt{(-8)^2 - (4)(0.25)(0)}}{2(0.25)}\)[/tex]


Sagot :

Let's start by analyzing the given quadratic equation: [tex]\(0 = 0.25x^2 - 8x\)[/tex]. This equation is in the standard quadratic form [tex]\(ax^2 + bx + c = 0\)[/tex].

Here, we have:
- [tex]\(a = 0.25\)[/tex]
- [tex]\(b = -8\)[/tex]
- [tex]\(c = 0\)[/tex]

We use the quadratic formula to find the roots of the equation:

[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]

Substituting in the values for [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]:

1. Calculate the discriminant [tex]\(b^2 - 4ac\)[/tex]:
[tex]\[ b^2 - 4ac = (-8)^2 - 4(0.25)(0) = 64 - 0 = 64 \][/tex]

2. Substitute [tex]\(b\)[/tex], the discriminant, [tex]\(a\)[/tex], and [tex]\(c\)[/tex] into the quadratic formula:
[tex]\[ x = \frac{-(-8) \pm \sqrt{64}}{2(0.25)} \][/tex]
[tex]\[ x = \frac{8 \pm \sqrt{64}}{0.5} \][/tex]

Hence, the correct equation that represents the solutions of [tex]\(0 = 0.25x^2 - 8x\)[/tex] is:

[tex]\[ x = \frac{8 \pm \sqrt{(-8)^2 - (4)(0.25)(0)}}{2(0.25)} \][/tex]

Thus, the correct choice is:
[tex]\[ x = \frac{8 \pm \sqrt{(-8)^2 - (4)(0.25)(0)}}{2(0.25)} \][/tex]